Petronas dan Hasil Royalti Minyak dan Gas Sarawak dalam Sistem Perkongsian Pengeluaran (1974-1990) - Suzanne Atar; A Rahman Tang Abdullah; Bilcher Bala (2018)
The petroleum oil product in Malaysia is under the jurisdiction and management of PETRONAS as provided under the Petroleum Development Act 1974. This act allows the establishment of PETRONAS, and granting exclusive rights to this corporation to control all exploration and exploitation activities ini Malaysia. It encompasses activities in the development of upstream and downstream oil and gas industries within the country. There are four petroleum-producing states, namely Sarawak, Sabah, Terengganu and Kelantan. However, the subject matter in question is the total distribution of oil and gas royalties of 5 percent paid by PETRONAS to the state government. In this regard, Sarawak has made this issue as a means for demanding a higher percentage of royalty, which arouse debates with the federal government. This is because Sarawak sees this oil revenue generates a substantial income each year, which should have given the state a greater percentage from 1974 to 1990. However, the understanding of this issue should be based on the PETRONAS's revenuebased framework which is subject to the petroleum fiscal regime, namely the Production Sharing Contract (PSC) system to generate sustainable profits. This paper aims to highlight the historical developments and procurement system adopted by PETRONAS in particular by focusing on the case of Sarawak.